Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae) - Dimitrova, Yana D.; Mariaux, Jean; Georgiev, Boyko B. (Zootaxa, 2017)
The genus Notopentorchis includes cestode parasites from swifts (Aves: Apodiformes: Apodidae and Hemiprocnidae). The following species are redescribed: N. micropus, previously known only from its original record from Apus affinis (Apodidae) in India, redescribed on the basis of specimens from the same host species in Gabon (new geographical record); N. vesiculigera, a widespread parasite of Palaearctic swifts, redescribed from A. affinis in Gabon (new host and geographical record); N. javanica and N. bovieni, both redescribed on the basis of their type series from Hemiprocne longipennis (Apodiformes: Hemiprocnidae) from Indonesia. Sphaeruterina caffrapi from Apus caffer from the Republic of South Africa, previously considered a synonym of N. javanica, is validated and transferred to Notopentorchis as N. caffrapi n. comb. Currently, Notopentorchis includes 8 species, all occurring in the Old World. An identification key to the species of Notopentorchis is presented.